2008
DOI: 10.1016/j.bone.2007.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of mobile and bound water by nuclear magnetic resonance correlate with mechanical properties of bone

Abstract: Since clinical measures of bone mineral density do not necessarily predict whether a person will fracture a bone without an intervention, there is a need to find supplementary tools for assessing bone quality. Presently, we hypothesized that measures of mobile and bound water by a Nuclear Magnetic Resonance (NMR) technique are correlated with bone strength and toughness, respectively. To test this, bending specimens from the mid-diaphysis of 18 human femurs were collected from 18 male donors and divided into m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(197 citation statements)
references
References 52 publications
(71 reference statements)
8
189
0
Order By: Relevance
“…(Although one of these previous studies [32] included soft-tissue signal suppression, which likely suppressed some portion of the pore water signal.) of bone (19,20). Low bound water measurements could account for the disproportionate increase in fracture risk compared with the decrease in bone density measurements in type 2 diabetes or in aging populations that have demonstrated increased brittleness that cannot be measured with current x-ray methods (27,28).…”
Section: Technical Developments: In Vivo Quantitative Mr Imaging Of Bmentioning
confidence: 99%
See 2 more Smart Citations
“…(Although one of these previous studies [32] included soft-tissue signal suppression, which likely suppressed some portion of the pore water signal.) of bone (19,20). Low bound water measurements could account for the disproportionate increase in fracture risk compared with the decrease in bone density measurements in type 2 diabetes or in aging populations that have demonstrated increased brittleness that cannot be measured with current x-ray methods (27,28).…”
Section: Technical Developments: In Vivo Quantitative Mr Imaging Of Bmentioning
confidence: 99%
“…These methods have no ionizing radiation and allow for new quantitative measurements that are known to reflect the material properties of bone (18)(19)(20).…”
Section: Technical Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H CPMG (CarrPurcell-Meiboom-Gill) pulse sequence is a NMR method which correlated with Laplace inversion analysis lead to a relaxation T 2 spectrum that can be used to determine the porosity and to assess the pore size distribution in bone [10]. There are just a few studies by NMR spectroscopy [11] or relaxometry [12] on rats' bones or rat optical nerve and frog sciatic nerve [13], but there are many studies of human cortical bone by 1 H NMR relaxometry in particular 1D T 2 distribution [14][15][16][17][18][19] or 2D T 2 -T 2 exchange maps [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…NMR spectroscopy measures the amount of water in different compartments in the bone, bound and mobile particularly. For example, Nyman et al [36] found that in men's bones the amount of bound water decreased with age, and the toughness decreased concomitantly. Synchrotron radiation can be used in various modes, either as a source of light to examine strains in the different components of bone [22] or for more straightforward tomography, producing images of relatively large specimens [52].…”
Section: New Methods For Characterizing Bonementioning
confidence: 99%